Significant cases of central cusps, enamel pits, and oral fibromas in tuberous sclerosis complex - Taga, Hitoshi; Yonenaga, Kazumichi; Eno, Yukiko; Yasumitsu, Tomohiro; Hatano, Takashi; Matsuo, Akira; Takato, Tsuyoshi (Odontology, 2021)
[Abstract] Tuberous sclerosis complex (TSC) is an autosomal dominant disorder in which benign nodular tumors form in the cerebral cortex, cerebellum, and throughout the body causing various symptoms. In this study, we summarized the incidence of dental findings in patients with TSC at our hospital and its association with diseases in various organs. Patients diagnosed with TSC at our hospital between January 2013 and September 2017, and who were examined in the dental and oral surgery department were included in this study. The presence of intraoral manifestations (central cusps, enamel pits, oral fibromas) was examined by means of visual inspection, intraoral photography, and X-ray photography. In addition, the relationship with associated diseases (neurological, cutaneous, cardiac, renal, and pulmonary) according to organ and disease severity was examined. The mean age (+- SD) of the 42 TSC patients (19 men and 23 women) was 27.8 +- 14.6 years, of which 24 patients (11 men and 13 women) presented with oral manifestations. Of these patients, seven had central cusps, 10 had enamel pits, and 17 had oral fibromas. The group with central cusps had significantly higher neurological issues in the relationship between intraoral manifestations and associated disease based on the involved organ. The prevalence of central cusps in TSC was 16.7%, which is significantly higher than the 2.6% reported in healthy Japanese subjects. The central cusp is a diagnostic factor alongside the presence of enamel pits and oral fibromas, which can aid in the early diagnosis of TSC by dentists.